2021
DOI: 10.3389/fphar.2021.724511
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Protects Sepsis Associated Damage to the Intestinal Mucosal Barrier Through the VDR/ Nrf2 /HO-1 Pathway

Abstract: Aims: Emodin is an anthraquinone extracted from Polygonum multiflorum, which has potential anti-inflammatory and anti-oxidative stress effects. However, the possible protective mechanism of emodin is unclear. The purpose of this study was to investigate the protective mechanism of emodin against cecal ligation and puncture and LPS-induced intestinal mucosal barrier injury through the VDR/ Nrf2 /HO-1 signaling pathway.Methods: We established a mouse model of sepsis by cecal ligation and puncture (CLP), and stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“… 143 Emodin from Polygonum multiflorum can also protect the colonic mucosal barrier through increases in the mRNA and protein expression of the VDR and its downstream molecules, Nrf2 and HO‐1. 144 Although these experiments demonstrate the protective effect of emodin, Cheng et al have found that its long‐term administration produces toxic metabolites, because colon microorganisms convert rhubarb anthraquinones to rhein, which accumulates over time and causes melanosis coli to increase the risk of colon cancer. 145 Shao et al indicated that Sophora flavescens Aiton EtOAc extract (SFE) inhibits oxidative stress and immune inflammation in UC mice, mainly manifested as linoleic acid, arachidonic acid, and fatty acid metabolism recovery, and reduces the expression of related inflammatory markers.…”
Section: Regulation Of the Intestinal Microbiota To Treat Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“… 143 Emodin from Polygonum multiflorum can also protect the colonic mucosal barrier through increases in the mRNA and protein expression of the VDR and its downstream molecules, Nrf2 and HO‐1. 144 Although these experiments demonstrate the protective effect of emodin, Cheng et al have found that its long‐term administration produces toxic metabolites, because colon microorganisms convert rhubarb anthraquinones to rhein, which accumulates over time and causes melanosis coli to increase the risk of colon cancer. 145 Shao et al indicated that Sophora flavescens Aiton EtOAc extract (SFE) inhibits oxidative stress and immune inflammation in UC mice, mainly manifested as linoleic acid, arachidonic acid, and fatty acid metabolism recovery, and reduces the expression of related inflammatory markers.…”
Section: Regulation Of the Intestinal Microbiota To Treat Ibdmentioning
confidence: 99%
“…In the experimental UC model, KD, through regulating the intestinal microbiota and reducing the level of TLR‐dependent phosphorylated PI3K/AKT/NF‐κB, protected the colonic mucosa 143 . Emodin from Polygonum multiflorum can also protect the colonic mucosal barrier through increases in the mRNA and protein expression of the VDR and its downstream molecules, Nrf2 and HO‐1 144 . Although these experiments demonstrate the protective effect of emodin, Cheng et al have found that its long‐term administration produces toxic metabolites, because colon microorganisms convert rhubarb anthraquinones to rhein, which accumulates over time and causes melanosis coli to increase the risk of colon cancer 145 .…”
Section: Regulation Of the Intestinal Microbiota To Treat Ibdmentioning
confidence: 99%
“…CYC can damage intestinal epithelial cells, resulting in increased intestinal permeability, impaired intestinal mucosal oxidation, and intestinal microbiota disorder, thus damaging intestinal immune function [ 30 , 31 ]. SOD activity can indirectly reflect the ability of scavenging oxygen free radicals, and MDA can be used to judge the level of oxygen free radicals in the colonic mucosa, the intensity of lipid peroxidation, and the degree of tissue damage [ 32 ]. Cai et al [ 33 ] found that alhagi honey polysaccharides significantly improve intestinal SOD activity, reduce MDA content, relieve intestinal oxidative stress injury, and the protect intestinal barrier in CYC mice.…”
Section: Discussionmentioning
confidence: 99%
“…NCM460 human colonic epithelial cells were purchased from Shanghai Meiwan Biotechnology Co., Ltd and grown in RPMI medium containing penicillin (100 U/ml)-streptomycin (100 U/ml) (Invitrogen, Carlsbad, CA, United States) and 10% fetal bovine serum (Hyclone, Logan, UT, United States) ( Zhou et al, 2018 ). Lipopolysaccharide (LPS, 10 ng/ml) was used to induce inflammation and autophagy in NCM460 cells ( Zeng et al, 2018 ; Ba et al, 2021 ; Guo et al, 2021 ; Shang et al, 2021 ). The groups were divided into control, LPS, LPS+HLD-DS, LPS+HLD-DS+3-MA, LPS+HLD-DS+RAPA, LPS+HLD-DS+PDTC, LPS+HLD-DS+PDTC+RAPA, and LPS+HLD-DS+PDTC+3-MA.…”
Section: Methodsmentioning
confidence: 99%